História e o caráter educativo do Museu Histórico da Irmandade da Santa Casa de Misericórdia do Estado de São Paulo - Araújo, José Cláudio de (2021)
The present study aims to understand the historical and educational character of the Museum of Brotherhood of the Holy House of Mercy of the State of São Paulo, from its museological organization, in June 2000 until 2019. In achieving this intent, priority was given to location, the selection and study of the records that the museum has, for this purpose we know the intricacies and the intentionality of its educational action, and we were able to obtain an understanding of the museological educational processes of that institution. When carrying out the analysis of the documentary sources contained in the museum's collection, it was possible to support the research base, listing sources that could count and structure the project. The research aimed to locate and analyze the educational elements that have been produced and are produced by identifying its history and seeking to establish the links between museological activities and teaching and learning activities that take place inside the Museum of Brotherhood of the Holy House of Mercy of the State of São Paulo. From a methodological point of view, the study was based on a critical review of the literature, mainly concerned with studies on school institutions, conducting interviews, collecting testimonials from their curators and teachers who used and regularly use this resource educational; institutional documents, photographs and utensils from the museum's collection were also used.